Age as a modifiable risk factor for cardiovascular disease - Sniderman, Allan D; Furberg, Curt D (The Lancet (British edition), 2008)
In developed countries, only after 60 years of age does the frequency of cardiovascular disease accelerate so dramatically that it eventually accounts for at least 40% of deaths.10 Most epidemiological studies in middle-aged populations follow participants for a relatively short time and therefore include only a small proportion of the total cardiovascular events that will eventually arise.